PENERAPAN MODEL SOLID UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK, BERPIKIR KRITIS, DAN KOLABORASI PADA MURID KELAS V SDN TELAGA BIRU 8. - Diana; Dwitalia Sari, Dessy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The poor levels of involvement, listening comprehension, critical thinking, and teamwork among fifth graders at SDN Telaga Biru 8 were the issue this study attempted to address. The SOLID learning approach, which combines Problem-Based Learning, Discovery Learning, and Numbered Heads Together, was developed to address these problems. The study's objectives were to characterize and evaluate teacher and student activities as well as look at ways that students' critical thinking, listening, teamwork, and learning outcomes had improved. 23 fifth graders participated in the three sessions of the study, which employed a qualitative methodology utilizing Classroom Action Research (CAR). Written tests, observations, and interviews were used to gather data. From the first to the third session, there were notable improvements in the findings. The score for teacher activity rose from 18 to 23. From 44% to 86%, the student in the class made progress. Critical thinking abilities from 52% to 95%, cooperation abilities from 56% to 95%, and listening abilities from 47% to 91%. Students' learning outcomes also improved as a result of these advancements, with cognitive performance rising from 56% to 95%, emotional performance from 52% to 91%, and psychomotor performance from 60% to 95%. These findings suggest that the SOLID learning approach is successful in raising learning outcomes, 21st-century skills, and student engagement.